Radio-frequency-transmitting hexagonal boron nitride-based anti- and de-icing heating system. Issue 42 (27th October 2020) - Hwang, Hyuntae; Ma, Kyung Yeol; Kim, Jae Won; Yuk, Dohun; Hong, Jiwon; Jung, Jun Hyuk; Yong, Seok-Min; Choi, Jaeho; Kim, Jin Young; Shin, Hyeon Suk
Abstract : The h-BN covered FTO wave patterns on a glass substrate can be used as a radio-frequency-transmitting heating system for de-icing. Abstract : Anti- and de-icing heating systems are used to both prevent the accumulation of ice and to remove it and thus avoid damage. Typically, anti- and de-icing heating systems employ carbon-based materials, metal frames, and bulky ceramic structures. These structures generally lead to the loss of radio-frequency (RF) signals and are also relatively heavy. Therefore, RF equipment such as radar domes (radomes) and antennas require anti- and de-icing systems with high RF transmittance for normal operation. In this work, we fabricated a fluorine-doped tin oxide (FTO) wave pattern covered with hexagonal boron nitride (h-BN) layers ( i.e., an h-BN/FTO wave pattern) on a glass substrate for use as an RF-transmitting heating system for anti- and de-icing. The FTO wave pattern and h-BN layer act as the heating element and heat spreader, respectively. The h-BN layer showed a transmittance of approximately 90% for RF waves on glass (X band: 8.2–12.4 GHz) (the 10% loss was attributable to the glass substrate). The differences in the temperatures of the FTO-patterned and non-patterned areas for the h-BN(3.6 nm)/FTO and FTO wave pattern were 19.3 and 25.5 °C, respectively. This means that the h-BN layer improved the heat-spreading performance by 6.2 °C. Furthermore, a de-icing test was performed using the h-BN(3.6 nm)/FTO wave pattern by applying a voltage of 40 V at −20 °C. The ice on the non-patterned area melted within 1 min while that on the FTO-patterned area melted within 30 s. These results suggest that the fabricated h-BN(3.6 nm)/FTO wave pattern for RF-transmitting heating systems is suitable for use with the radomes of drones, unmanned aerial vehicles, aircraft, and spaceships in extremely cold environments.